2021
DOI: 10.14444/8165
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Unilateral Biportal Endoscopic Decompression for Degenerative Lumbar Canal Stenosis

Abstract: Background: The unilateral biportal endoscopic (UBE) technique provides minimally invasive decompression for degenerative lumbar canal stenosis (DLCS). With appropriate control of the hydrostatic pressure of normal saline irrigation, the surgery can be performed in a clear and magnified surgical field through 2 small surgical wounds.Methods: A review of published literature in PubMed was performed to identify studies of UBE decompression for DLCS. The outcome measures include operation time, length of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…It has been reported that the complication rates with endoscopic decompression for lumbar spine stenosis range from 5.5% to 13.8%, with dural tear having the highest incidence. 18 In one of the studies, incidental durotomy was observed in 8.6% of cases 20-21. Çavuşoğlu and colleagues 22 reported that incidental durotomy is almost between 3.5 to 12% of the cases. Kim et al common complication in their study was dural tear (7.2%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been reported that the complication rates with endoscopic decompression for lumbar spine stenosis range from 5.5% to 13.8%, with dural tear having the highest incidence. 18 In one of the studies, incidental durotomy was observed in 8.6% of cases 20-21. Çavuşoğlu and colleagues 22 reported that incidental durotomy is almost between 3.5 to 12% of the cases. Kim et al common complication in their study was dural tear (7.2%).…”
Section: Discussionmentioning
confidence: 92%
“…1 In a review study it was observed that the operation time for endoscopic bilateral decompression from a unilateral approach was 72 minutes. 18 In another such study, the average duration of the surgery was 89 ± 56.9 minutes (range, 50 -190 minutes). 6 The mean duration of surgery in our study was 56 minutes (range 35 -86 minutes).…”
Section: Discussionmentioning
confidence: 95%
“…UBE surgery has significant advantages, such as a good operative view, easy surgical manipulation, reduced blood loss, and decreased postoperative back pain. It has been considered a minimally invasive technique with favorable clinical outcomes and high patient satisfaction ( 17 ). For nonfusion endoscopic spinal surgery, the preservation of facet joints on the pathological side is the most crucial consideration ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, unilateral biportal endoscopy (UBE) has generated a wave of frenzied learning. It has an independent working and viewing portal, with the freer operation and higher decompression efficiency, which well overcomes the shortcomings of insufficient decompression in previous endoscopic surgery (11,12). And the feasibility of UBE with unilateral laminotomy for bilateral decompression (ULBD) in the treatment of LSS has been confirmed to provide satisfactory clinical results (13,14).…”
Section: Introductionmentioning
confidence: 96%